Toward an intelligent tutoring system :a case study on ssx 1012 tamadun Islam and tamadun Asia 1 - Jamalludin, Bujang; Mohamad Rozman, Besiri; Sinarwati, Mohamad Suhaili (University Malaysia Sarawak (UNIMAS), 2001)
The internet provides an infrastructure that supports unprecedented communication capabilities and collaboration opportunities. The unique features and possibilities of the Internet such as hypertext and hypermedia, numerous websites with good quality sources of information, drastic development in electronic commerce, digital broadcasting and transfer, collaboration tools, are variable working together to create a fascinating environment where in diverse teaching and learning experiences can be developed.